Detection of proteome changes in human colon cancer induced by cell surface binding of growth-inhibitory human galectin-4 using quantitative SILAC-based proteomics - Michalak, Malwina; Warnken, Uwe; André, Sabine; Schnölzer, Martina; Gabius, Hans-Joachim; Kopitz, Jürgen (Journal of proteome research, 2016)
Endogenous lectins have the capacity to translate glycan-encoded information on the cell surface into effects on cell growth. As test cases to examine changes in protein presence associated with tumor growth inhibition, we applied SILAC-based proteomics on human colon carcinoma cells treated with galectin-4 (Gal-4). The five tested lines—LS 180, Vaco 432, Colo 205, CX 1, and HCT 116—responded with differentiation and reduced proliferation to Gal-4 binding. In proteomic analysis (mass spectral data deposited with PRIDE, PXD003489), 2654 proteins were quantified, of which 190 were down-regulated and 115 were up-regulated (>2-fold). 1D annotation analysis of the results indicated down-regulation of DNA replication-associated processes, while protein presence for secretory and transport functions appeared increased. The strongest induction was found for CALB2 (calretinin; ∼24-fold), TGM2 (protein-glutamine γ-glutamyltransferase 2; ∼11-fold), S100A3 (∼10-fold), and GSN (gelsolin; 9.5-fold), and the most pronounced decreases were seen for CDKN2A (tumor suppressor ARF; ∼6-fold), EPCAM (epithelial cell adhesion molecule; ∼6-fold), UBE2C (ubiquitin-conjugating enzyme E2 C; ∼5-fold), KIF2C (kinesin-like protein KIF2C; 5-fold), and LMNB1 (lamin-B1; ∼5-fold). The presence of the common proliferation marker Ki-67 was diminished about 4-fold. By tracing significant alterations of protein expression likely relevant for the observed phenotypic effects, the capacity of a galectin to affect the proteome of human colon cancer cells at multiple sites is revealed.
Gesehen am 30.04.2020